Uso de herramientas de tecnología de información y comunicación para diagnóstico y seguimiento de diabetes mellitus en el cantón Yacuambi durante junio-noviembre 2012 - Maldonado Alarcón, Antonia Adriana (2014)
Establish the use of ICT tools for diagnosis and monitoring of diabetes mellitus in the population of Canton Yacuambi through mobile medical clinics in remote diagnosis in order to generate changes in the statistical data of the area. Descriptive study was conducted with a quantitative design, the sample were people who came to the health post May 28, Tutupali, La Esperanza and Jembuentza, in which risk factors were identified. The risk factors for diabetes mellitus for mobile tele-medical diagnosis sessions are age 34%, 24% female predominance. And lower prevalence of women with children over 4 kg at birth 10%. 100% of health workers use ICT tools to support for care and diagnostic means. It identifies the physical media are one of the main barriers of communication for the diagnosis and monitoring. Where diabetes mellitus is the tenth leading cause of morbidity in 2012 in Canton Yacuambi.